Sensory Processing Difficulties in Opsoclonus-Myoclonus Syndrome: A Pilot Project of Presentation and Possible Prevalence. (July 2016) - Green, Dido; Lim, Ming; Lang, Bethan; Pohl, Keith; Turk, Jeremy
Opsoclonus-myoclonus syndrome is a rare but serious neurological condition resulting in loss of control of eye movements, often accompanied by difficulties in posture and movement control with reports of sensory sensitivities potentially impacting on behavior. This pilot study characterizes the presence of atypical sensory behaviors in opsoclonus-myoclonus syndrome through questionnaire survey of a cohort of families. The Short Sensory Profile, Vineland Adaptive Behavior Scale, and Developmental Behaviour Checklist were distributed to 30 families; 16 were returned anonymously. Atypical sensory behaviors were identified in a large proportion (62.5%). Children reported as being more anxious showed greater sensitivity to auditory stimuli, U (14) 11, P = .026. This is consistent with recent recognition of more extensive disease neurocognitive effects in Opsoclonus-myoclonus syndrome. Further research is needed to increase understanding of the complex pathology of this disease and to provide indicators for sensory and behavioral as well as pharmacological interventions.